Cinnamomum burmannii EXTRACT ENHANCES GLUT1 EXPRESSION AND PROMOTES GROWTH IN HYPERGLYCEMIC ZEBRAFISH EMBRYOS VIA ALDOSE REDUCTASE INHIBITION: IN SILICO AND IN VIVO STUDY - Nurfaizah Titisari Sulihah; Editya Fukata; Theakirana Firdaus; Fitrah Aulia Lisabilla (Majalah Kesehatan, 2026)
Cinnamomum burmannii extracts possess antidiabetic effects by stimulating glucose transporter expression (GLUT), particularly GLUT1, which plays a critical role in facilitating cellular glucose uptake and maintaining glucose homeostasis. Additionally, aldose reductase (AR) is an enzyme that is crucial in the development of secondary diabetic complications, and its inhibition is associated with modulation of GLUT1 expression. However, the molecular mechanisms of C. burmannii in modulating the AR–GLUT1 axis and its impact on recovering hyperglycemia-induced growth impairment remain poorly understood. This study aimed to determine the effect of CB on GLUT-1 expression and body length in hyperglycemic model zebrafish embryos through possible binding to AR. Zebrafish embryos were divided into five experimental groups: embryonic media (EM)-treated group as control, 4% glucose, and 4% glucose + C. burmannii  extracts in concentrations of 1.25, 5, and 10 µg/mL. All groups were exposed at 3-72 hours after fertilization (hpf). The hyperglycemic model was confirmed by phosphoenolpyruvate carboxykinase (PEPCK) overexpression. The mRNA expression of GLUT1 and PEPCK was measured by reverse transcription-PCR, and body length measurement was performed using ImageJ. Computerized molecular docking was conducted to determine the interaction between several C. burmannii extract main constituents (cinnamaldehyde, trigonelline, epicatechin, and 3,4-dihydroxycinnamic acid) and AR using PubChem, Protein Database, Pymol, Discovery Studio, and Pyrx software. Epalrestat (AR inhibitor) was used as a control ligand. Exposure of C. burmannii extracts to hyperglycemic zebrafish embryos resulted in a significant increase in GLUT1 expression (p = 0.004) and body length (p = 0.000) with the optimal dose at 1,25 and 10 µg/mL, respectively. Molecular docking showed that 3,4-dihydroxycinnamic acid has high binding affinity (-8.1 kcal/mol), which was stronger than Epalrestat (-7.1 kcal/mol). Collectively, these findings indicate that C. burmannii  extract may improve hyperglycemia-induced developmental impairment by enhancing GLUT1 expression, potentially through modulation of aldose reductase activity.